ACTION OF AVIPATTI CHURNAM: AN AYURVEDIC PERSPECTIVE - Rajalekshmy.P.R; Delvin.T.Robin (International Journal of Applied Ayurved Research, 2016)
Virechana is one of the effective treatment modality in paittika rogas especially skin ailments. The most widely used virechana yoga is Avipatti churna. An analysis of the yoga reveals the magical blend of Ayurvedic combination of various drugs. Each and every drug in Avipatti churna is meant for a purpose which needs to be evaluated on the basis of its pharmacodynamics. The young doctors who prescribe medicines without understanding the logic behind the ayurvedic combinations are in a way spoiling the science.